Emerging Pollutants in the Environment: Occurrence, Fate, Risk Assessment and Degradation Methods - Qingwei Bu; Yuning Ma (Toxics)
The use of chemical substances has brought great benefits to human well-being; however, the dark side of the coin is that they may pose risks to human health and the environment [...]